‘We’re Here Because We’re Here’: Trench Culture in the Great War - Seal, Graham (Taylor & Francis/ The Folklore Society, 2013)
English-speaking soldiers of the Great War created a large ‘trench press’, a body of periodicals by, for, and about their experiences. They contain a wealth of folkloric material and indications of its significance and functions. While acknowledging the constraints involved in retrieving once-living traditions from the fragmentary survival of mostly makeshift periodicals, this article describes and discusses the processes involved in the creation and development of an especially well-defined folk culture in unprecedented and extreme circumstances. While some elements of soldier folklore, especially song, verse, and language, have been the subject of usually discrete interest by folklorists, this is the first attempt to understand a range of folkloric practice and expression in the context of a particular set of combat circumstances.